A surface confined yttrium(iii) bis-phthalocyaninato complex: a colourful switch controlled by electrons. Issue 8 (11th May 2016) - Alcón, I.; Gonidec, M.; Ajayakumar, M. R.; Mas-Torrent, M.; Veciana, J.
Abstract : SAMs of a Y(iii ) double-decker complex on ITO have been prepared and their electrical and optical properties explored, exhibiting three accessible stable redox states with characteristic absorption bands in the visible spectra, corresponding to three complementary colors ( i.e., green, blue and red). Abstract : SAMs of a Y(iii ) double-decker complex on ITO have been prepared and their electrical and optical properties explored, exhibiting three accessible stable redox states with characteristic absorption bands in the visible spectra, corresponding to three complementary colors ( i.e., green, blue and red). These absorption bands are exploited as output signals of this robust ternary electrochemical switch, behaving hence as an electrochromic molecular-based device.